Mucinous cystadenoma of the appendix: a diagnostic dilemma. - Chaudhary P, (Department of Surgery, UKM Medical Centre, 2014)
Mucinous cystadenoma of appendix is a rare clinical entity. We here report a case of an elderly male who presented in surgery outpatient department for routine check-up. Ultrasonography followed by CT scan of the abdomen did not give any conclusive diagnosis, following which exploratory laparotomy was done which was suggestive of appendiceal mucocele. The aim of reporting this case was to review the various clinical presentations and an optimum management of such incidental tumors.